Isolation, structure elucidation, and antidiabetic test of vicanicin compound from lichen Teloschistes flavicans - Maulidiyah Maulidiyah, Akhmad Darmawan, Asriani Hasan, Dwiprayogo Wibowo, La Ode Agus Salim, Ansharullah Ansharullah, Faizal Mustapa, Ishmah Farah Adiba Nurdin, Muhammad Nurdin (Journal of Applied Pharmaceutical Science, 2020)
Teloschistes flavicans is a lichen genus of the Teloschistaceae family with the orange-yellow color making it a very distinctive species. Recently, T. flavicans has been used as a natural medicinal ingredient because it contains several secondary metabolites to treat diseases. Thus, the aim of this study is to show the antidiabetic activity and isolation of secondary metabolite compounds from T. flavicans. Extraction, separation, and purification were conducted by using acetone solvent and separation was conducted by using column gravity combined with thin layer chromatography. Based on these results, we discovered the secondary metabolites of T. flavicans by the appearance of pure white crystal needles. Moreover, it was tested using liquid chromatography-mass spectroscopy/MS, Fourier-transform infrared spectroscopy, and 1D-NMR spectroscopy (1H and 13C) and comparison with several studies shows that the secondary metabolite vicanicin was obtained with the molecular formula C18H16Cl2O5. Subsequently, the antidiabetic activity of T. flavicans was investigated by estimating the level of non-enzymatic antioxidants from α-glucosidase with an IC50 value of 197.04 μg/ml. This research provides a perspective on the natural products of lichen T. flavicans, which have the potential as antidiabetic medicine.
Keywords: Lichen,Teloschistes flavicans, antidiabetic,α-glucosidase, vicanicin.